The impact of corruption on ESG based on EU countries - Pluskota, Anna (Ekonomia i Prawo. Economics and Law, 2024)
Motivation: The impact of corruption on core ESG measures for EU countries has not yet been studied. There are few analyses in the literature on the relationship between corruption and ESG from a ma-cro level, and only such analyses allow an indication of the costs of corruption and the effects from fighting it at the country level. Aim: The study aims to ocean the impact of corruption on ESG measures: CO2 emissions, life expectancy and economic growth in the EU. Calculating the cost of corruption is key to properly assessing the effectiveness of anti-corruption projects. Results: The effect of corruption on ESG measures was shown to be heterogeneous. A non-linear relationship between corruption and CO2 and economic growth was shown, while the relationship between corruption and life expectancy was linear. The impact of corruption on ESG should be considered from the point of view of the ESG component variable in question, rather than on the basis of synthetic ESG measures.